Decoherence in neutrino oscillation at the ESSnuSB experiment - The ESSnuSB collaboration; J. Aguilar; M. Anastasopoulos; E. Baussan; A. K. Bhattacharyya; A. Bignami; M. Blennow; M. Bogomilov; B. Bolling; E. Bouquerel; F. Bramati; A. Branca; et al. (Journal of High Energy Physics)
Abstract Neutrino oscillation experiments provide a unique window in exploring several new physics scenarios beyond the standard three flavour. One such scenario is quantum decoherence in neutrino oscillation which tends to destroy the interference pattern of neutrinos reaching the far detector from the source. In this work, we study the decoherence in neutrino oscillation in the context of the ESSnuSB experiment. We consider the energy-independent decoherence parameter and derive the analytical expressions for P μe and P μμ probabilities in vacuum. We have computed the capability of ESSnuSB to put bounds on the decoherence parameters namely, Γ21 and Γ32 and found that the constraints on Γ21 are competitive compared to the DUNE bounds and better than the most stringent LBL ones from MINOS/MINOS+. We have also investigated the impact of decoherence on the ESSnuSB measurement of the Dirac CP phase δ CP and concluded that it remains robust in the presence of new physics.